2013
DOI: 10.1007/s11103-013-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of rice (Oryza sativa L.) E3-ubiquitin ligase OsHOS1 gene in the modulation of cold stress response

Abstract: Plants can cope with adverse environmental conditions through the activation of stress response signalling pathways, in which the proteasome seems to play an important role. However, the mechanisms underlying the proteasome-mediated stress response in rice are still not fully understood. To address this issue, we have identified a rice E3-ubiquitin ligase, OsHOS1, and characterized its role in the modulation of the cold stress response. Using a RNA interference (RNAi) transgenic approach we found that, under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Sequence homology searches have identified homologous OsHOS1, OsICE1, and OsDREB1s genes in the rice genome (17)(18)(19). Similar to what has been observed in Arabidopsis, OsHOS1 is able to regulate the protein abundance of OsICE1 (19). Also, the expression of OsDREB1A and OsDREB1B is induced by cold stress, and overexpression of these two genes increases the cold stress tolerance of transgenic rice (20), which suggests that the CBF/DREB1 cold signaling pathway is conserved in rice.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Sequence homology searches have identified homologous OsHOS1, OsICE1, and OsDREB1s genes in the rice genome (17)(18)(19). Similar to what has been observed in Arabidopsis, OsHOS1 is able to regulate the protein abundance of OsICE1 (19). Also, the expression of OsDREB1A and OsDREB1B is induced by cold stress, and overexpression of these two genes increases the cold stress tolerance of transgenic rice (20), which suggests that the CBF/DREB1 cold signaling pathway is conserved in rice.…”
supporting
confidence: 61%
“…Sequence homology searches have identified homologous OsHOS1, OsICE1, and OsDREB1s genes in the rice genome (17)(18)(19). Similar to what has been observed in Arabidopsis, OsHOS1 is able to regulate the protein abundance of OsICE1 (19).…”
supporting
confidence: 57%
“…In rice, another member of the DREB1 regulon, OsDREB1B (CBF1), also shows rapid induction in response to touch stimulus (Figueiredo et al, 2012). It is therefore possible that members of the DREB1 regulon, such as OsDREB1A and OsICE1 (both regulated by OsHOS1; Lourenço et al, 2013), are not only responsible in the response to abiotic stress but also in the response to mechanical stimuli. In rice, the ubiquitination and proteasome pathway have been implicated in root development through the modulation of rice ROOT ARCHITECTURE ASSOCIATED1 (Ge et al, 2004;Han et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrate that the rice root curling phenotype depends on a mechanical barrier and is modulated by JA. We have generated transgenic rice lines silencing the expression of OsHOS1 (RNA interference [RNAi]:: OsHOS1; Lourenço et al, 2013). When rice seedlings were grown in test tubes for 10 d after germination (DAG) in liquid Yoshida's nutritional medium (Yoshida et al, 1976), RNAi::OsHOS1 seedlings showed a straight root phenotype, whereas wild-type seedlings showed a root curling phenotype (Fig.…”
mentioning
confidence: 99%
“…20 E3-ubiquitin ligase OsHOS1 functioned in the modulation of cold stress response, 21 while the SINA E3 ligase OsDIS1 played a negative role in drought-stress tolerance through the regulation of stress-related genes by post-translational regulation of OsNek6 in rice. 22 Thus, RING proteins seem to be key regulatory components of stress tolerance and therefore can be considered as candidate genes for enhancing stress tolerance in crops.…”
mentioning
confidence: 99%